(Im)mobilization and speciation of lead under dynamic redox conditions in a contaminated soil amended with pine sawdust biochar. (February 2020) - Beiyuan, Jingzi; Awad, Yasser M.; Beckers, Felix; Wang, Jianxu; Tsang, Daniel C.W.; Ok, Yong Sik; Wang, Shan-Li; Wang, Hailong; Rinklebe, Jörg
Graphical abstract: Highlights: Biochar produced at 550 °C (BC550) remarkably reduced dissolved Pb under dynamic Eh . The dissolved Pb fluctuated with varied Eh due to redox chemistry of Fe/Mn oxides. BC550 is the best for Pb immobilization under varied Eh in the current study. Higher pyrolysis temperatures make biochars more suitable for dynamic Eh situation. Abstract: Biochar can reduce the mobility and availability of potentially toxic elements (PTEs) in soils and improve soil properties. However, immobilization efficiencies of biochar can be varied according to environmental conditions, such as pH and redox potential ( Eh ), especially for soils under flood-dry cycles. In the current study, biochar produced at 300 and 550 °C (referred as BC300 and BC550, respectively) and its feedstock (pine sawdust biomass, BM) were used to amend a lead (Pb)-contaminated soil under pre-defined redox windows (from −300 to +250 mV). Key features of the soil-solution were evaluated in detail, including pH, dissolved organic carbon, sulphate, and dissolved Al, Fe, and Mn. The BC550 reduced the amount of dissolved Pb and showed a different pattern of Eh -pH in the soil slurry compared with BM and BC300. This might be attributed to its higher alkalinity and surface area. The highest amount of dissolved Pb was found at slightly anoxic conditions (−100 to 0 mV) in CS (control soil), S&BM (soil amended with BM), and S&BC300 (soil amended with BC300), which could be associated with the dissolution of Fe/Mn oxides. Moreover, the fitting results of Pb X-ray absorption fine structure (XAFS) indicated that the proportion of Pb(CH3 COO)2 was decreasing when changing from anoxic to oxic condition in S&BC300, while the Pb speciation pattern in soil was stable in S&BC550. These results suggested that BC550 is more suitable amendment for Pb immobilization than BM and BC300 in this study. In addition, biochar produced at higher temperatures can be more stable so it can be suitable for remediation of Pb-contaminated soils which are frequently flooded.